2019
DOI: 10.1055/s-0039-1687914
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Vasopressor Use in Free Flap Surgery: A Systematic Review and Meta-Analysis

Abstract: Background The use of vasopressors in free flap surgery has traditionally been avoided due to the presumed risk of pedicle vasospasm leading to flap failure. However, there is a lack of strong clinical evidence to suggest that their administration during microvascular surgery is absolutely contraindicated. The aim of this study is to clarify the impact of perioperative vasopressor use on free flap outcomes. Methods A systematic review was performed of all English-language articles that have compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 59 publications
(165 reference statements)
1
42
2
4
Order By: Relevance
“…This controversy likely stems from the conventional theory that vasoactive drugs may result in vasospasm, decreased flap perfusion, and subsequent flap failure in a denervated flap ( Godden et al, 2000 ; Harris et al, 2012 ; Goh et al, 2019 ). Of note, these postulations are primarily based on experimental animal models with conflicting results ( Table 2 ) ( Banic et al, 1997 ; Cordeiro et al, 1997 ; Massey and Surgery, 2007 ; Lecoq et al, 2008 ; Scholz et al, 2009 ; Eley et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This controversy likely stems from the conventional theory that vasoactive drugs may result in vasospasm, decreased flap perfusion, and subsequent flap failure in a denervated flap ( Godden et al, 2000 ; Harris et al, 2012 ; Goh et al, 2019 ). Of note, these postulations are primarily based on experimental animal models with conflicting results ( Table 2 ) ( Banic et al, 1997 ; Cordeiro et al, 1997 ; Massey and Surgery, 2007 ; Lecoq et al, 2008 ; Scholz et al, 2009 ; Eley et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in the only animal study to specifically examine the effects of flap perfusion in a free flap model, Banic et al, demonstrated no adverse effects on pedicle blood flow or free flap microcirculation with the systemic use of phenylephrine ( Banic et al, 1997 ). Thus, the use of vasopressors intraoperatively may actually increase flap perfusion due to improved overall MAP without significant deleterious effects from sympathectomy ( Rizzoni et al, 2000 ; Goh et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations